THE IMPLEMENTATION OF REGIONAL GOVERNMENT POLICIES IN IMPROVING ISLAMIC EDUCATION QUALITY AT MANDAILING NATAL DISTRICT - Siti Hawa Lubis; Fachruddin Azmi; Saiful Akhyar Lubis (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study aims to discover the participation of the regional government of Mandailing Natal District on the development of Islamic education in this area. This is descriptive research with no number at all in describing data. The data are taken from the interview with all stakeholder or the district of Mandailing Natal including the head of district, Regional Secretary of Madailing Natal District, the head of Ministry of Religious Affairs of Madailing Natal and also the treasure of Madailing Natal District. The findings show that Mandailing Natal district allocates budget for developing Islamic education trough advising on religious particularly in advising the Islam religion. Furthermore, Mandiling government gives the land for developing building of The State Collage for Islamic Studies of Madailing Natal. Moreover, advising for Islamic teacher is as well programmed by Mandailing government to increase the capacity and quality of Islamic teacher in this district. However, due to Islamic institution is under authority of the ministry of Religious Affairs and centered from Jakarta, regional government could not allocated more budget to defray all operational need of Islamic education institution. Therefore, it should be find some resolution from regulation and political will of the national government or regional government